Uticaj kreditnog rizika na finansijski rezultat banke - Radojević, Tijana; Kesić, Marina; Rajin, Danica; Butėnas, Ričardas (The European Journal of Applied Economics, 2023)
The appearance of credit risk is one of the key dangers for the banking portfolio, because if it becomes impossible to collect claims from several key clients, the bank could remain insolvent. Recent financial crises have highlighted the need for banks to identify, measure, assess and control credit risk, as well as to ensure an adequate level of capital to cover potential losses in the event of loan defaults. Therefore, risk management relies heavily on the direct application of mathematical and statistical methods and models, as well as on the use of their results for business purposes. The aim of this paper is to gain knowledge about the effect of credit risk on financial performance of bank in a changing world, bearing in mind that credit risk management is one of the indicators of the results of banking operations of a certain bank.